An empirical examination of over-subscription in the Malaysian IPO market - Tajuddin, Ahmad Hakimi; Mohd Rashid, Rasidah; Abdullah, Nur Adiana Hiau; Abdul Rahim, Ruzita (Universiti Putra Malaysia, 2015)
This paper examines the effects of the involvement of informed investors and the presence of information asymmetry in fixed price mechanism on over-subscription ratio in the Malaysian initial public offerings (IPO).Analyzing the data on 373 IPOs listed on Bursa Malaysia from 2000 to 2012, we find an insignificant positive relationship between informed investors and over-subscription.However, the relationship between information asymmetry and over subscription is strongly negative.The negative effect of company size suggests that big companies that are considered to have lower information asymmetry receive less investors’ interest, as investments in low risks companies are expected to provide lower initial returns.